Test rig development for high pressure spray - Mohd Azahan, Mohd Yusuff (2010)
Automotive technology is very important to people now days. It can help us to move freely where we want to in very short time. Automotive technology is very fast growing at the moment because of the importance in human life.So an experiment of improvement needs to be carrying on consecutively to the system especially in fuel system in order to make sure the effectiveness of the system. On behalf of this the place to conduct an experiment is needed to ease the researching process. In this report, the models of the test rig that are already in the market is discussed. Besides that, it is also explain about the materials that will be used in making and build the test rig which is suitable to the equipment and apparatus on it. A briefly explanation about the problems faced while completing this project is also state in this report. Also to the good ideas that are generated to an improvement of the test rig for high pressure spray given in this report to future improvement.